Exploring talent identification and recruitment at circus arts training and performance organizations - Bailey, A.; MacMahon, C. (High Ability Studies, 2018)
The purpose of this study was to contribute to newly emerging research within the area of circus arts. The more specific aim was to explore talent identification and recruitment processes in this area. A total of six participants involved in the selection, identification, and recruitment of circus artists undertook semi-structured, in-depth qualitative interviews. The participants were sampled from three different circus arts training and performance organizations. The results provide an overview and contrast of the talent identification and recruitment processes involved in an international performance-based circus, a national training and performance-based circus, and a youth training and performance-based circus. The findings show the complex and changing requirements for the domain of circus from fundamental skills, to developing skills for performance, and then skills for innovation, and echo the call to support transitions between performance levels (Burtt & Lavers, 2017). This research builds a strong foundation for continued exploration to understand the complexity of this area of training and performance.